2017
DOI: 10.1016/j.actamat.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooling rate after solution treatment on subsequent phase separation during aging of Fe-Cr alloys: A small-angle neutron scattering study

Abstract: The effect of cooling rate after solution treatment on the initial structure of concentrated binary Fe-Cr alloys and the effect of the initial structure on phase separation during subsequent aging has been investigated. The nano-scale compositional fluctuations in the bulk of the alloys are studied using small-angle neutron scattering and the results are compared with simulations using the Cahn-Hilliard-Cook (CHC) model. The alloys investigated represent different mechanisms of phase separation and at higher C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…[22,27,56,57] The degree of phase separation would then primarily depend on the time spent within the miscibility gap, i.e., the cooling rate achieved. [49,58,59] Second, a positive short-range order (SRO) factor for Cr compositions above 10 at. pct may result in some Cr clustering above the miscibility gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22,27,56,57] The degree of phase separation would then primarily depend on the time spent within the miscibility gap, i.e., the cooling rate achieved. [49,58,59] Second, a positive short-range order (SRO) factor for Cr compositions above 10 at. pct may result in some Cr clustering above the miscibility gap.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the mirror sectors were included. separation were then obtained by removing the contribution of the background and normalizing it with respect to B fit i.e., SðQÞ [36] The wavelength of the a and a¢ phase separation i.e., distance between the two a¢ domains was obtained as follows [23,26,27,44,49,50] :…”
Section: Small-angle Neutron Scattering (Sans)mentioning
confidence: 99%
“…Zhou et al [11] showed that Cr atoms clustered in the solutionized condition of a Fe-46.6%Cr alloy, where this clustering decreased with increasing solutionizing temperature. Xu et al [12] also studied binary Fe-(20-40)% Cr alloys in furnacecooled and brine-quenched conditions and showed that the initial state of phase separation may have a significant effect on the outcome of subsequent aging. Lemoine et al [13] also mentioned the progression of spinodal decomposition during quenching of a cast DSS alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental, nondestructive techniques have been developed to measure some key information needed for multiscale models at the macro‐ and micro‐scales. Small‐angle neutron diffraction can be used to nondestructively measure statistical information of micro‐defects . A neutron stress spectrometer can be used to measure the stress in situ and nondestructively …”
Section: Introductionmentioning
confidence: 99%